1992
DOI: 10.1007/bf02368519
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the dynamic ventilatory response to hypoxia in humans

Abstract: A two-component dynamic model was used to describe the ventilatory response to sustained hypoxia in humans. One component (Xs) represents the stimulating effects of hypoxia and the other component (Xd), the hypoxic ventilatory decline. The total ventilatory response to hypoxia is represented by the sum of the two components. A nonlinearity is included to account for the nonlinear steady-state ventilatory response to hypoxia. A sensitivity analysis of the model indicates that, with a step change in F(ETO2) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A sensitivity analysis of a proposed model will indicate whether the parameter values of the model can be estimated with finite precision from the measured data. 20 The parameters may not be estimable for various reasons: because of the model structure, dependence on other parameters, or the specific input function chosen. We performed a sensitivity analysis of simulated data in which C REM increases to 5 ng/ml in five steps using three distinct input functions: (1) step size ϭ 1 ng/l, duration of step ϭ 1 min; (2) step size ϭ 1 ng/ml, duration of step ϭ 5 min; and (3) step size ϭ 1 ng/ml, duration of step ϭ 0.1 min.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…A sensitivity analysis of a proposed model will indicate whether the parameter values of the model can be estimated with finite precision from the measured data. 20 The parameters may not be estimable for various reasons: because of the model structure, dependence on other parameters, or the specific input function chosen. We performed a sensitivity analysis of simulated data in which C REM increases to 5 ng/ml in five steps using three distinct input functions: (1) step size ϭ 1 ng/l, duration of step ϭ 1 min; (2) step size ϭ 1 ng/ml, duration of step ϭ 5 min; and (3) step size ϭ 1 ng/ml, duration of step ϭ 0.1 min.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…They are considered a critical defense mechanism to preserve oxygen delivery to the brain. The response to both isocapnic and poikilocapnic hypoxia has been well characterized in humans and animals (42,149,206,551,740). Duffin et al (150) first showed a selective depression of the peripheral chemoresponse by halothane compared to barbiturates in man.…”
Section: Effects On the Acute Hypoxic Ventilatory Responsementioning
confidence: 98%
“…In the awake human, even moderate hypoxia causes swift hyperventilation (206,740). The response to acute hypoxia originates from the peripheral chemoreceptors in the CB.…”
Section: Effects On the Acute Hypoxic Ventilatory Responsementioning
confidence: 99%